GROWTH AND PHYSIOLOGICAL CHARACTERISTICS OF SOYBEAN GENOTYPES (Glycine max L.) TOWARD SALINITY STRESS - Nurul Aini; Syekhfani Syekhfani; Wiwin Sumiya Dwi Yamika; Runik Dyah P.; Adi Setiawan (AGRIVITA Journal of Agricultural Science, 2014)
The research aimed to determine the tolerance limit of soybean genotypes toward salinity stress, plant growth and physiological characteristics. It was conducted in green house, from April to August 2013. The study involved two activities.  The first activity for evaluating a salinity stress, consisted of four levels of soil salinity (EC): 0.9; 4; 7; 10 dS m-1 and eleven genotypes. The second one to obtain information about changes in physiological and morphological characteristics of soybean affected by salinity stress. The second activity concisted of two soil salinity levels (EC): 1.52 dS m-1 and 8.58 dS m-1. The results showed that at salinity 10 dS m-1, all varieties/genotypes were not able to survive until the age of 43 days after sowing (DAS). At salinity 4 dS m-1, total plant dry weight of most geno-types soybean decreased by 48.14%, while the salinity of 7 dS m-1 total plant dry weight of all soybean decreased by 64.89%. Concentration of K and Na in soybean leaves were higher than those in soybean root tissue. The content of K and Na in leaves and roots of most soybean genotypes increased as soil salinity increased from 1.52 to 8.58 dS m-1, except for genotype G11. Keywords: leaf chlorosis, necrosis, salinity tole-rant, soybean genotype